2006
DOI: 10.1248/bpb.29.1408
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Betula platyphylla var. japonica on Proteoglycan Release, Type II Collagen Degradation, and Matrix Metalloproteinase Expression in Rabbit Articular Cartilage Explants

Abstract: Osteoarthritis (OA) is a degenerative joint disease characterized by the progressive loss of articular cartilage, subchondral bond remodeling, spur formation, synovial inflammation, and in particular, the degradation of proteoglycan and collagen. The integrity of these macromolecules is vital to cartilage and joint function. 1)Proteoglycan is a component of the articular cartilage extracellular matrix, providing it with many of its characteristic physicochemical properties.2) The carbohydrate component of aggr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…It has been effective and safe during its long history of human use (Huh, 1999;Kim, 2000). Previously our studies reported that Betula platyphylla extracts prevented cartilage degradation in cartilage explants culture (Cho et al, 2006), and the n-butanol fraction of Betula platyphylla also decreased cartilage alternations through balance of MMPs/TIMP-1 in vivo model of osteoarthritis without toxicity . The degree of inflammation was evaluated on a scale from 0 to 5 by two pathologists blinded to the treatments.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…It has been effective and safe during its long history of human use (Huh, 1999;Kim, 2000). Previously our studies reported that Betula platyphylla extracts prevented cartilage degradation in cartilage explants culture (Cho et al, 2006), and the n-butanol fraction of Betula platyphylla also decreased cartilage alternations through balance of MMPs/TIMP-1 in vivo model of osteoarthritis without toxicity . The degree of inflammation was evaluated on a scale from 0 to 5 by two pathologists blinded to the treatments.…”
Section: Discussionmentioning
confidence: 64%
“…It has been reported that the bark extract of Betula platyphylla has antioxidant and anticancer activities (Ju et al, 2004). We previously reported that the bark extract of Betula platyphylla inhibits the degradation of proteoglycan and collagen through the down regulation of MMP-3 and MMP-13 expressions and activities without affecting the viability or morphology of IL-1␣-stimulated rabbit articular cartilage explants (Cho et al, 2006). Following bioactivity-guided fractionation, the most potent cartilage-protective fraction from the bark of Betula platyphylla (BFBP) (the n-butanol fraction) was identified using the GAG assay in cartilage rabbit explant cultures; the reported BFBP has been shown to have protective effects against cartilage degradation in a collagenase-induced osteoarthritis rabbit model .…”
Section: Introductionmentioning
confidence: 89%
“…The bark of AWB contains betulin, several triterpenes and phenolic compounds, such as diarylheptanoids and arylbutanoids, as active compounds. It has been reported that lupane triterpens from the bark of AWB have antiviral activity and that the extract of the bark of AWB has antioxidant, anticancer, hepatoprotective, chondroprotective and superoxide scavenging activities (Matsuda et al, 1998;Baltina et al, 2003;Zhang et al, 2003;Ju et al, 2004;Cho et al, 2006). However, it has not yet been studied if and how AWB suppresses the development of AD.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the bark extract of Betula platyphylla has antioxidant and anticancer activity (Ju et al, 2004). We previously reported that the bark extract of Betula platyphylla inhibits the degradation of proteoglycan and collagen through the down regulation of MMP-3 and MMP-13 expression and activities without affecting the viability or morphology of IL-1␣-stimulated rabbit articular cartilage explants (Cho et al, 2006). Following the bioactivity-guided fractionation, the most potent cartilage protective fraction, n-butanol fraction from the bark of Betula platyphylla (BFBP), had been identified using GAG assay in cartilage explant culture of rabbit.…”
Section: Introductionmentioning
confidence: 90%